1999
DOI: 10.1007/s004360050509
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of three oocyst extracts of Cryptosporidium baileyi in experimentally infected chickens

Abstract: The immunogenic properties of water-soluble and detergent-extracted components of Cryptosporidium baileyi oocysts were studied. Oocyst cytosol antigen (OCA) containing hydrophilic proteins was obtained by freeze-thaw cycles in liquid nitrogen. This was followed by Triton X-114 extraction of remaining oocyst fragments to dissolve membrane-bound proteins (TRE). The remainder of the pellet was solubilized with sodium dodecyl sulfate and treated with 2-mercaptoethanol to reduce disulfide-linked oocyst wall protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Antigens used by other workers (8) were also evaluated for the production of antibodies to the oocyst surface. The mice immunized with OCA and TRE preparations showed no response to the oocyst wall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Antigens used by other workers (8) were also evaluated for the production of antibodies to the oocyst surface. The mice immunized with OCA and TRE preparations showed no response to the oocyst wall.…”
Section: Discussionmentioning
confidence: 99%
“…Groups of five BALB/c (ARC) female mice 8 to 12 weeks old were immunized by intraperitoneal injection (i.p.) with either an oocyst wall preparation, whole oocysts, soluble protein extract, or the three preparations described by Hornok et al (8). Each preparation in PBS was emulsified with an equal volume of Freund complete adjuvant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, the cell-mediated response is the predominant form of immunity against cryptosporidiosis. In studying the vaccine potential of an extract of C. baileyi oocysts, Hornok et al (1999) observed that chickens injected intramuscularly with the extract developed partial resistance to oral challenge, but those inoculated orally with live oocysts became completely resistant. However, the antibody responses of these two groups were identical 3 weeks after challenge, suggesting that serum antibodies had negligible effect on the development of protective immunity.…”
Section: Avian Immune Responses To Cryptosporidiummentioning
confidence: 99%